Community Knowledge and Attitudes about the Health Protocols Implementation during the COVID-19 Pandemic in North Birobuli Village - Rasyika Nurul Fadjriah; Muhammad Jusman Rau; Firmansyah Firmansyah; Nurfiana Nurfiana; Sadli Syam (Journal of Health and Nutrition Research, 2022)
The purpose of the study was to determine the knowledge and attitudes of the community about implementing health protocols during the COVID-19 pandemic in North Birobuli Village. The research method used was qualitative with a case study approach. The number of informants in the study was 12 people obtained through purposive sampling. The results showed that the predisposing factors for knowledge related to COVID-19, symptoms of COVID-19, the transmission of COVID-19, how to prevent COVID-19, and health protocols could be mentioned well by informants. However, the public still had a negative attitude towards COVID-19, who thought that COVID-19 does not exist and did not believe; in this attitude predisposing factor, the informant also explained that he was starting to feel tired of implementing health protocols. Our finding concludes that the community already has fairly good knowledge regarding health protocols during the covid 19 pandemic, and the community's attitude is showing negative attitudes related to covid and feeling tired regarding applying the health protocol.